Information and Communication Technology (ICT): An Aid to Adult Education Methodology in Promoting Teaching and Learning Activities in Rural Communities - Comfort Wuraola Adeyemo (Newinera Publisher, 2021)
This paper view information and communication technology (ICT) as an aid to adult education methodology in promoting teaching and learning activities in rural communities in Nigeria. The paper reviews the concept of adult education and the existing methodologies used in the delivery of adult education programmes. It also examines the various ICT devices that can be used to complement adult teaching methodology. The technological devices considered in this paper includes: mobile phones, projectors, slides with moving pictures, radio, television, computer/ laptops and internet facilities. The paper discusses the benefits of using these devices alongside adult teaching methodology to enhance effective teaching and learning activities in rural communities. The paper concludes that incorporating these devices into adult teaching methodology, particularly in rural communities would promote active learning, enhance critical thinking skills of adult learners, create awareness, facilitate learning and develop rural communities. The paper therefore suggests that; governments should provide necessary equipment and internet facilities in rural communities to aid adult’s teaching and learning activities. Also, quality technological devices should be made available in all the adult education centers to promote teaching and learning activities. Lastly, regular trainings, conferences and seminars should be organized for facilitators and workers on the use of ICT devices to improve teaching and learning activities.